Effects of Helicobacter pylori infection on intestinal microbiota, immunity and colorectal cancer risk - Engelsberger, Veronika; Gerhard, Markus; Mejías-Luque, Raquel (Frontiers in Cellular and Infection Microbiology, 2024)
Infecting about half of the world´s population, Helicobacter pylori is one of the most prevalent bacterial infections worldwide and the strongest known risk factor for gastric cancer. Although H. pylori colonizes exclusively the gastric epithelium, the infection has also been associated with various extragastric diseases, including colorectal cancer (CRC). Epidemiological studies reported an almost two-fold increased risk for infected individuals to develop CRC, but only recently, direct causal and functional links between the chronic infection and CRC have been revealed. Besides modulating the host intestinal immune response, H. pylori is thought to increase CRC risk by inducing gut microbiota alterations. It is known that H. pylori infection not only impacts the gastric microbiota at the site of infection but also leads to changes in bacterial colonization in the distal large intestine. Considering that the gut microbiome plays a driving role in CRC, H. pylori infection emerges as a key factor responsible for promoting changes in microbiome signatures that could contribute to tumor development. Within this review, we want to focus on the interplay between H. pylori infection, changes in the intestinal microbiota, and intestinal immunity. In addition, the effects of H. pylori antibiotic eradication therapy will be discussed.